Why don't mice lacking the mitochondrial Ca2+ uniporter experience an energy crisis?. (11th October 2018) - Wang, Pei; Fernandez‐Sanz, Celia; Wang, Wang; Sheu, Shey‐Shing
Abstract: Current dogma holds that the heart balances energy demand and supply effectively and sustainably by sequestering enough Ca 2+ into mitochondria during heartbeats to stimulate metabolic enzymes in the tricarboxylic acid (TCA) cycle and electron transport chain (ETC). This process is called excitation‐contraction‐bioenergetics (ECB) coupling. Recent breakthroughs in identifying the mitochondrial Ca 2+ uniporter (MCU) and its associated proteins have opened up new windows for interrogating the molecular mechanisms of mitochondrial Ca 2+ homeostasis regulation and its role in ECB coupling. Despite remarkable progress made in the past 7 years, it has been surprising, almost disappointing, that germline MCU deficiency in mice with certain genetic background yields viable pups, and knockout of the MCU in adult heart does not cause lethality. Moreover, MCU deficiency results in few adverse phenotypes, normal performance, and preserved bioenergetics in the heart at baseline. In this review, we briefly assess the existing literature on mitochondrial Ca 2+ homeostasis regulation and then we consider possible explanations for why MCU‐deficient mice are spared from energy crises under physiological conditions. We propose that MCU and/or mitochondrial Ca 2+ may have limited ability to set ECB coupling, that other mitochondrial Ca 2+ handling mechanisms may play a role, and that extra‐mitochondrial Ca 2+ may regulate ECB coupling. Since the heart needs to regenerate a significant amount of ATP to assure the perpetuation of heartbeats, multiple mechanisms are likely to work in concert to match energy supply with demand. Abstract : We propose that MCU and/or mitochondrial Ca 2+ may have limited ability to set ECB coupling and that other mitochondrial Ca 2+ handling mechanisms and/or extra‐mitochondrial Ca 2+ may regulate ECB coupling. The diagram shows the major mitochondrial Ca 2+ handling processes (influx and efflux) and the role of intra‐ and extra‐mitochondrial Ca 2+ in regulating cardiac bioenergetics. AP, action potential; C, cytochrome C; Q, co‐enzyme Q; I‐V, the five complexes of electron transport chain; LCC, L‐type Ca 2+ channel; Pi, phosphate; ΔΨm, mitochondrial membrane potential. Please refer to the text for the other abbreviations.